Legal Protection of Land Assets of Waqf Muhammadiyah and Nahdlatul Ulama in Magelang District - Kustiana, Septi; Puji Sulistyaningsih; Dakum; Tsuroyyaa Maitsaa’Jaudah (Universitas Darussalam Gontor, 2024)
**English**The legal protection of Waqf land is regulated in the Republic of Indonesia Act No. 41 of 2004 on Waqf. Waqf assets in Indonesia generally often have very varied disputes. Thus, the purpose of this research is to analyze the efforts to protect the assets of Wakf Muhammadiyah and Nahdlatul Ulama in the Magelang district in keeping the land Wakf so that it is safe and there is no dispute. This research method uses field research, the primary and secondary sources of data used in this research. It is then analyzed decipherably and presented qualitatively. The results of this research are the first is the protection of the legal assets of the waqf land carried out by the Assembly of Governors of the Muhammadiyah District (MPW PDM) Magelang and the Foundation of the Governor of Nahdlatul Ulama (LWPNU) of the district of Magelang to conduct the management, utilization, and development of the waqf land properly. Secondly, if there are obstacles or obstacles in the process of protecting the law of the waqf land, then there should be a deeper socialization of the waqf, monitoring and evaluation in the implementation of the law protection as well as collaborative communication between the relevant agencies. **Indonesia**Perlindungan hukum tanah wakaf diatur dalam Undang-Undang Republik Indonesia Nomor 41 Tahun 2004 tentang Wakaf. Aset wakaf di Indonesia secara umum sering terjadi sengketa yang sangat bervariasi. Dengan demikian tujuan penelitian ini menganalisis upaya perlindungan aset tanah wakaf Muhammadiyah dan Nahdlatul Ulama di Kabupaten Magelang dalam menjaga tanah wakaf agar aman dan tidak terjadi sengketa. Metode penelitian ini menggunakan studi lapangan (field research), sumber data yang digunakan yaitu primer dan sekunder yang berkaitan dengan penelitian ini. Selanjutnya dianalisis secara deksriptif dan disajikan secara kualitatif. Hasil penelitian ini yang yang pertama yaitu perlindungan hukum aset tanah wakaf yang dilakukan oleh Majelis Pemberdayaan wakaf Pimpinan Daerah Muhammadiyah (MPW PDM) Magelang dan Lembaga Wakaf Pimpinan Nahdlatul Ulama (LWPNU) Kabupaten Magelang yakni melakukan pengelolaan, pemanfaatan, dan pengembangan tanah wakaf secara baik. Kedua, adanya kendala atau hambatan dalam proses upaya perlindungan hukum tanah wakaf maka harus diadakan sosialisasi tentang wakaf lebih mendalam, monitoring dan evaluasi dalam pelaksanaan perlindungan hukum serta komunikasi yang kolaboratif antara lembaga yang bersangkutan.